Women, Reconciliation Right and Gender Justice in Islam Family Law - Aswiyanto Aswiyanto (IAIN Pekalongan, 2019)
Religious teachings are considered to have long oppressed women. Teachings having been dominated by men have been used as justifications for the perception of society that is very detrimental to women. This article discusses the gap of understanding on women's rights to reconcile with their husband who have divorced them, viewed from the perspective of Islamic scholars and Islamic law. In this case, the Qur'an has the principle that the positions of men and women are equal as a servant, because men and women are created from the same substance (min nafsin waahidah), the same task (khalifatullah filardh), and have same obligations (liya'budun). However, Muslim scholars agree that the reconciliation is absolutely the husband’s right. In gender perspective, women can apply for reconciliation (Rujuk) as their rights to their husbands. This study conducts analysis using a content analysis approach related to the issue of reconciliation rights dominated by men (husbands) by means of redeeming the husband's rights that have been given to them. And in the presence of khulu, the wife also has the right of reconciliation (Rujuk) to the husband who has divorced her.